Minimally invasive percutaneous plate osteosynthesis versus intramedullary nail fixation for distal tibial fractures: a systematic review and meta-analysis - Bo Wang; Yang Zhao; Qian Wang; Bin Hu; Liang Sun; Cheng Ren; Zhong Li; Kun Zhang; Dingjun Hao; Teng Ma; Yao Lu (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background The treatment for distal tibial fractures remains controversial to date. Minimally invasive percutaneous plate osteosynthesis (MIPPO) and intramedullary nailing (IMN) are well-accepted and effective methods for distal tibial fractures, but these methods were associated with complications. This study aimed to assess and compare the clinical and functional outcomes in patients with distal tibial fractures treated with MIPPO or IMN. Methods We systematically reviewed randomized controlled trials (RCTs) that compared MIPPO with IMN in patients with distal tibial fractures from inception till 15 August 2019. Also, quantitative summaries of time to reunion, rate of complications, and functional outcomes were evaluated. Results The pooled results suggested that patients in the MIPPO group had a longer time to reunion with a mean difference of 1.21 weeks [P = 0.02; 95% confidence interval (CI) 0.16–2.26)] than those in the IMN group. The overall union complications and deep infection between IMN and MIPPO were similar (P > 0.05). IMN had a significantly low risk of wound complications [risk ratio (RR) = 0.51, P = 0.00, 95% CI 0.34–0.77)]. The pooled functional outcomes of the two groups remained controversial by different evaluating scores. Conclusions Compared to MIPPO, IMN had a significantly low risk of wound complications and associated with limited time for reunion. Although the pooled functional outcomes of the two groups were controversial due to different evaluating scores, IMN was the preferred surgical technique than MIPPO for treating distal tibial fractures.